How could entertainment content marketing affect intention to use the metaverse? Empirical findings - Malek Alsoud; Ali Trawnih; Husam Yaseen; Tha'er Majali; Anas Ratib Alsoud; Omar Abdel Jaber (International Journal of Information Management Data Insights)
Despite the metaverse's potential to transform digital business, there remains a scarcity of research investigating on how content marketing affects users' intention to use the metaverse. This study aimed to identify if entertainment content marketing affects users to adapt the metaverse. by adapting the Spice framework, incorporating variables like continuity, sense of presence, interoperability, concurrence, and economic flow. Data was collected via an online survey of 454 online gamers from Jordan who were purposefully selected. Structural equation modelling using partial least squares analysis revealed that all five factors positively affected metaverse intention. Overall, the study contributes to the knowledge by examining the Spice Framework in the context of metaverse technologies. Beyond the academic realm, our findings carry practical significance for marketers, policymakers, and stakeholders shaping the dynamic landscape of digital interactions within the metaverse.